Being suspicious in the workplace: the role of suspicion and negative views of others in the workplace in the perception of abusive supervision. Issue 4 (6th April 2021) - Schyns, Birgit
Abstract : Purpose: Research reported in this manuscript focuses on the relationship between trait suspicion and the perception of abusive supervision. Based on previous research, the authors assume that suspicion is positively related to the perception of abusive supervision. The role implicit theories play in this relationship is examined. Design/methodology/approach: Two studies are presented to examine the relationship between trait suspicion and the perception of abusive supervision as moderated by implicit leadership theories. The first study is a survey study, and the second study is an experimental vignette study. Findings: Results of both studies indicate that suspicion is positively related to the perception of abusive supervision and that implicit leadership theories moderate the relationship between suspicion and the perception of abusive supervision. Research limitations/implications: Results are interpreted in terms of biases in leadership perception as well as the reversing-the-lens perspective. Originality/value: While there is progress in taking into account follower characteristics and the resulting perceptual biases in the study of constructive leadership phenomena such as transformational leadership, less is know about the follower perception aspect of destructive leadership phenomena. With this research, the authors extend research into the influence of follower characteristics on the perception of abusive supervision and also look at boundary conditions of this relationship by including implicit leadership theories as a moderator.